English and Indonesian Nominalization: A Case of Word Classes - Sulaiman, Masagus; Syahri , Indawan (Yayasan Corolla Education Centre, 2022)
This research aims at determining the similarities, dissimilarities, and possible learning difficulties faced by students learning English and Indonesian nominalization as well as the recommendations to TEFL. The qualitative research design was applied. The documentation technique was used to collect the data. To analyze the data, the researchers used a descriptive analysis. The results showed that there were three similarities and four the dissimilarities between English and Indonesian nominalization found. The three similarities were in suffixation, demonstrative pronominal and conversion. While, the four dissimilarities were in affixation, Adjective reduplication, conversion and To-infinitive. The possible learning difficulties faced by students learning English and Indonesian nominalization was suffixation and confixation which were not very familiar with them. The recommendations of this research was as a fundamental teaching guidance in helping English teachers design a better teaching Grammar on nominalization (word classes), in terms of affixation, Adjective reduplication, conversion and To-infinitive. Keywords: Contrastive Analysis (CA), Nominalization, Word Classes